Resolver el problema abierto: Teñir lanas a partir de productos colorantes naturales. Una actividad investigativa para la enseñanza secundaria obligatoria - Martínez Aznar, M. Mercedes; Ovejero Morcillo, P. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
We present in this paper a class work for solving investigative problems, inserted into the theoretical constructivist context. We have chosen the topic «Dye wool with natural dyers», for its relevance in Organic Chemistry and also for its cultural and social interest, showing an actual perspective of Science. On the other hand, we develop the class performance with emphasis in assessment.